PENYELESAIAN SENGKETA SECARA DAMAI DALAM PERSPEKTIF HUKUM INTERNASIONAL - Cahya Palasari; Ni Putu Rai Yuliartini (Jurnal Komunikasi Hukum, 2022)
The purpose of writing this article is to explain how to resolve international disputes that are being faced by countries. There are many solutions in a country to resolve an international dispute and it all depends on each country in this writing there is a peaceful dispute resolution and in this dispute resolution it can also be through an international court. In this dispute case, parties from other countries who have no interest cannot participate in this case in any form.